2014
DOI: 10.2169/internalmedicine.53.1104
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestation of Hypercalcemia Caused by Adrenal Insufficiency in Hemodialysis Patients: A Case-series Study

Abstract: Objective The goal of this study was to clarify the clinical manifestation of hypercalcemia due to hypoadrenalism in hemodialysis (HD) patients. Methods We retrospectively analyzed the clinical characteristics of five HD patients who had presented with hypercalcemia due to adrenal insufficiency (age: 69±7 [58-75] years old, time on HD: 13±11 [2-32] years). We conducted corticotropin-releasing hormone (CRH) and adrenocorticotropic hormone (ACTH) stimulation tests. We also examined serum bone turnover markers be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Whereas most studies had the aim of investigating the responsiveness of the hypothalamo-pituitary-adrenal axis in asymptomatic patients on HD, three studies tested for adrenal insufficiency due to clinical suspicion. The case series of Sakao et al reported AI as a secondary cause for hypercalcemia [ 24 ]. Arregger et al and Koh et al performed adrenal function testing due to hypotension in HD patients [ 9 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas most studies had the aim of investigating the responsiveness of the hypothalamo-pituitary-adrenal axis in asymptomatic patients on HD, three studies tested for adrenal insufficiency due to clinical suspicion. The case series of Sakao et al reported AI as a secondary cause for hypercalcemia [ 24 ]. Arregger et al and Koh et al performed adrenal function testing due to hypotension in HD patients [ 9 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…ACTH testing was performed in seven of the retrieved 16 studies, but in none of these during ongoing HD [ 6 , 20 , 22 , 24 , 26 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical suspicion of adrenal insufficiency was high in 8/10 patients, and treatment with hydrocortisone resulted in hemodynamic improvement in seven. Sakao et al (2014) in Japan analyzed retrospectively the clinical characteristics of five HD patients who were presented with hypercalcemia due to adrenal insufficiency (age: 69±7), time on HD: 13±11years old. All patients had critical illnesses at hypercalcemia onset, with at least one symptom, such as eosinophilia, hypoglycemia, or fever.…”
Section: Introductionmentioning
confidence: 99%